Influence of restricted mastication on swallowing function - Hayashi, Hiroki; Kusunoki, Takayuki; Komiyama, Osamu; Hamada, Yoshihiro; Kawamoto, Akiyo; Takahashi, Kazuya; Shimada, Akiko (Journal of Oral Rehabilitation, 2024)
Background Oral food processing is an important part of daily food intake. A major part of this process is mastication, which prepares a bolus of food for swallowing by mechanically crushing and grinding ingested food between the teeth using rhythmic movements. Masticatory dysfunction is common in the elderly and in some neurological disorders and can have serious negative health consequences. Objective This study investigated the effect of restricted mastication, achieved by experimentally reducing the duration of mastication, on masticatory patterns and subsequent swallowing function. Methods Thirty healthy men (25 ± 3 years old) were instructed to chew gum jelly with a free mastication duration (G100), a half and a quarter duration of G100. Masseter and digastric electromyographic (EMG) activity was recorded to assess mastication and swallowing activity, respectively. In addition, the acceleration of the thyroid cartilage ridge was measured with an accelerometer. The root mean square (RMS) of muscle EMG activity in the masseter and digastric muscles, the number of masseter EMG bursts, time to peak and total duration of each masseter EMG burst, swallowing duration and laryngeal elevation latency were analysed. Results Restricting masticatory duration reduced the number of mastication cycles (p < .001), prolonged the time to peak (p < .001) and total duration of masseter EMG bursts (p < .001) and resulted in an overall increased RMS score of masseter muscle activity (p = .017). Furthermore, restricted masticatory duration led to a decrease in both swallowing duration (p = .001) and laryngeal elevation latency (p = .012), with a significant increase in the RMS score of digastric muscle activity (p < .001). Conclusions Under the experimental conditions of restricted mastication, several adaptation features were observed, including changes in masticatory cycle characteristics and swallowing duration. Thus, although the overall masticatory efficiency was reduced, these adaptations allowed healthy individuals to still swallow safely.